1998
DOI: 10.2307/1132206
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering Changes in Parent-Child Conflict across Adolescence: A Meta-Analysis

Abstract: A series of meta-analyses addresses whether and how parent-child conflict changes during adolescence and factors that moderate patterns of change. The meta-analyses summarize results from studies of change in parent-child conflict as a function of either adolescent age or pubertal maturation. Three types of parent-adolescent conflict are examined: conflict rate, conflict affect, and total conflict (rate and affect combined). The results provide little support for the commonly held view that parent-child confli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
204
2
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(224 citation statements)
references
References 3 publications
12
204
2
6
Order By: Relevance
“…Moreover, mothers and daughters in the current sample did significantly differ on how heated they reported conflict to be, with girls reporting more intensity in conflict than mothers. This finding was consistent with early-adolescent research findings in the parent-child conflict literature (Laursen et al, 1998), suggesting that some differences in perceptions of parent-child conflict exist prior to adolescence and hence may not be indicative of changing relationships during that developmental period.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, mothers and daughters in the current sample did significantly differ on how heated they reported conflict to be, with girls reporting more intensity in conflict than mothers. This finding was consistent with early-adolescent research findings in the parent-child conflict literature (Laursen et al, 1998), suggesting that some differences in perceptions of parent-child conflict exist prior to adolescence and hence may not be indicative of changing relationships during that developmental period.…”
Section: Discussionsupporting
confidence: 88%
“…Parent-child conflict across the toddler and early preschool years is often frequent and an important arena for children's socialization (e.g., Dunn & Slomkowski, 1992). Similarly, early adolescence is often a time of increased emotional and physical distancing from parents (e.g., Paikoff & Brooks-Gunn, 1991;Steinberg, 2001), as well as a time during which the frequency and affective intensity of parent-child conflicts may be higher than at other ages (Laursen, Coy, & Collins, 1998). But what is happening between parents and children during middle and late childhood?…”
mentioning
confidence: 99%
“…Unexpectedly, however, the proportion of memories showing parent conflict did not decline across adolescence. Methodological factors may have partly contributed to the difference between the present findings and those of past research (e.g., Laursen et al, 1998). Whereas past research used survey and interview data to assess rates of conflict, the present study used retrospective narratives about momentous events.…”
Section: Discussioncontrasting
confidence: 58%
“…A recent meta-analysis found that the rate of conflict with parents lessened across adolescence (Laursen, Coy, & Collins, 1998), possibly because of greater success at balancing autonomy and connectedness with parents. We therefore examined the relative prevalence of conflict in memories about parents and peers, as well as changes in conflict with the age of the remembered event.…”
Section: Conflict In Adolescent Relationshipsmentioning
confidence: 99%
“…In addition, a meta-analysis showed that conflict affect increased from early to middle adolescence and stabilized during late adolescence in between the levels of the two former age periods (Laursen et al 1998). The increase in conflict during early adolescence was longitudinally confirmed (McGue et al 2005).…”
Section: Development Of Support Conflict and Powermentioning
confidence: 87%